Applying Reflective Practice-Based Learning (RPL) Principles in Clinical Education - Schwartzlose, Lone Lindstrøm; Nielsen, Jannie Schmidt; Jensen, Trine Fritzner; Bundgaard, Stine Bylin (Proceedings for the European Conference on Reflective Practice-based Learning 2025, 2025)
This paper explores how the six fundamental principles of Reflective Practice-Based Learning (RPL) (Horn et al., 2020) can be applied to clinical supervision in health education. Based on an action research project with clinical educators from physiotherapy and occupational therapy programmes, we examine how RPL can strengthen reflective learning processes during clinical placements. A workshop was designed and facilitated following RPL’s fundamental principles, using practice-based cases and structured dialogues to engage clinical educators in reflection on real-life supervisory challenges. The workshop aimed to foster educators’ capacity to support students’ professional development by creating reflective learning environments that integrate theory and practice. Drawing on a social constructionist approach to knowledge and narrative analysis, we present empirical findings from a reflective team session and analyse the data through the lens of selected RPL fundamental principles. The narrative highlights how educators navigate the balance between dialogue, collaboration, and appropriate disturbance when guiding students from reflection to action. Findings indicate that applying RPL principles enhances clinical educators’ ability to tailor supervision to students’ readiness, particularly when students hesitate to engage in practice. The study contributes to the development of supervision practices that recognise reflection as both a cognitive and practical process, requiring sensitivity, adaptability, and professional judgement.